PEDAGOGICAL CONDITIONS OF TRAINING FUTURE PRIMARY SCHOOL TEACHERS BASED ON THE TIMSS INTERNATIONAL ASSESSMENT PROGRAM (Conferencea, 2022)
This article describes the theoretical importance and content of training future primary school teachers based on the TIMSS international assessment program.